Re-Design of Nablus Municipality Building - Janem, Areen; Ghanem, Sereen; Ammar, We’am (My University, 2018)
The Municipality in Palestine plays a big role in the development and growth in various aspects. Particularly, Nablus city is considered one of the most crowded cities in Palestine that is rapidly developing and growing. And due to the importance of municipality in this city which should be strong and effective. The Municipality of Nablus was chosen to be re-designed in architectural, structural, environmental, mechanical and electrical aspects in order to meet the design standards. The integrated design has been done after a long series of analysis and evaluation the building which has been done in graduation project "1". The architectural design has been done according to specifications and standards for functions, areas, relationships with site analysis and environmental solutions considering daylight evaluation and improvement of shading systems and insulating the building. For the structural design, it has been done using software programs to achieve the purpose of seismic design. Mechanical design has been done by choosing the appropriate HVAC, water and fire systems. Electrical design has also been done using software for lighting and sockets. At the end, it could be said that an integrated strong design for the Municipality reflects the development of its performance in the society.